2017
DOI: 10.12659/msm.902612
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Microagiopathy of Oral Mucosa Depends on Disease Duration and Therapy

Abstract: BackgroundDiabetes mellitus is a chronic degenerative systemic disease whose prevalence is increasing. This paper aims to evaluate the effects of diabetic microangiopathy, depending on its duration and the type of treatment administered, by using polarized light videocapillaroscopy of the oral mucosa.Material/MethodsWe enrolled 120 subjects: 60 healthy subjects and 60 patients with diabetes mellitus. In turn, patients were divided into 3 subgroups according to the type of diabetes, the duration of the disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(11 reference statements)
1
5
1
Order By: Relevance
“…The immunity of the DM patient is more compromised, particularly for long duration DM as a result of micro-and macro-vascular complications as well as the treatment tolerance of the disease 28 . Indeed much is known about the duration of the DM implying the complication and severity of the diseases as well as the terminal outcome, either in the general complication or especially in the TB occurrence [29][30][31] .The present study did not provide evidence of a longer duration of DM as a risk factor for pulmonary TB, because of the interaction of household contact (OR=63.3) as the most influential factor. In this study, the proportion of shorter duration of DM was higher in the subjects with household contact group compared to the negative contact group (Figure 2).…”
Section: Discussioncontrasting
confidence: 74%
“…The immunity of the DM patient is more compromised, particularly for long duration DM as a result of micro-and macro-vascular complications as well as the treatment tolerance of the disease 28 . Indeed much is known about the duration of the DM implying the complication and severity of the diseases as well as the terminal outcome, either in the general complication or especially in the TB occurrence [29][30][31] .The present study did not provide evidence of a longer duration of DM as a risk factor for pulmonary TB, because of the interaction of household contact (OR=63.3) as the most influential factor. In this study, the proportion of shorter duration of DM was higher in the subjects with household contact group compared to the negative contact group (Figure 2).…”
Section: Discussioncontrasting
confidence: 74%
“…In the event that microangiopathy is generalized, an important contribution can be ascribed to the study of peripheral microcirculation and therefore also to the study of oral microcirculation [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oral mucosa, in fact, has many advantages compared to other sites (periungual fold, conjunctival mucosa, dermis) [ 13 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 The structural alterations in microvasculature may be detected with available imaging methods. Scardina et al 27 in polarized light videocapillaroscopy revealed microangiopathic changes in oral mucosa in patients with T1D and T2D, which included reduced density and altered length and diameter of the loops and increased density of the periodontal capillaries. The most significant changes were noted in patients with T1D and correlated with disease duration.…”
Section: Pathomechanisms Linking Diabetes and Periodontal Diseasementioning
confidence: 99%
“…The most significant changes were noted in patients with T1D and correlated with disease duration. 27 Recent studies found the associations of periodontal disease with microvascular complications of diabetes. The significant association between diameters of retinal venules and severe periodontitis was found in patients with diabetes, but not in patients with severe periodontitis and no diabetes.…”
Section: Pathomechanisms Linking Diabetes and Periodontal Diseasementioning
confidence: 99%